2006
DOI: 10.1055/s-2006-950387
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis of the Skull Base and Neck in a Patient with AIDS and Non-Hodgkin's Lymphoma

Abstract: Necrotizing fasciitis is a rapidly progressing, life-threatening soft tissue bacterial infection found more frequently in immunocompromised subjects and rarely in the head and neck. We report a rare case of a patient with acquired immunodeficiency syndrome (AIDS) and non-Hodgkin's lymphoma (NHL) who presented with a high fever and supraorbital cellulitis 1 week after undergoing chemotherapy. He received intravenous antibiotic therapy but soon developed dyspnea and trismus with rapid extension of the cellulitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
1
4
1
Order By: Relevance
“…We found that 57% of HIV-associated NF hospitalizations required ICU care. Use of ICU was mentioned in 4 patients described in prior case reports of HIVassociated NF [7,8,11,13]. Our findings are similar to those reported by Widjaja et al [27] and Das et al [24], showing need for ICU care in 63% and 56% of their patients, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We found that 57% of HIV-associated NF hospitalizations required ICU care. Use of ICU was mentioned in 4 patients described in prior case reports of HIVassociated NF [7,8,11,13]. Our findings are similar to those reported by Widjaja et al [27] and Das et al [24], showing need for ICU care in 63% and 56% of their patients, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The site of infection was described inconsistently in case reports of NF in HIV-infected patients. Two case reports indicated NF involving limbs [5,13], while cervical infection was described in 3 patients [7,10,11], and breast involvement in one [14]. While the small number of patients precludes meaningful analysis, the available data from these cases suggest involvement of uncommon body sites in patients with HIV-associated NF.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations